Improving the Recovery of Coarse-Coal Particles by Adding Premineralization Prior to Column Flotation. Issue 2 (4th March 2017) - Ni, Chao; Jin, Mingguo; Chen, Yuran; Xie, Guangyuan; Peng, Yaoli; Xia, Wencheng
ABSTRACT: A premineralization process, a pipe flow mineralization method adopted by adding a self-aspirated bubble generator in the feed pipe, was developed to improve the recovery of coarse-coal particles using a flotation column. The recoveries of various size fractions, including -700+600, -600+500, -500+250, -250+74, and -74 μm, using a conventional column (CC), a premineralization column (PMC), and a conventional column combined with the premineralization process (PM-CC) were investigated. According to the results, the CC showed a good performance in recovering coal particles with sizes below 250 μm, but a poor recovery of particles of sizes above 250 μm. The PM-CC presented advantages in recovering coal particles in contrast with the CC, especially coarse coal particles. Compared with the CC, the combustible recovery of -700+600, -600+500, -500+250, -250+74, and -74 μm size fractions obtained with the PM-CC was increased by 17.69, 17.15, 10.37, 0.58, and 4.07 percentage points, respectively, and the combustible recovery of the clean coal increased by 9.29 percentage points. The ash content of clean coal obtained with the PM-CC was almost identical to that of the CC. It was an effective way that adding the premineralization process prior to column flotation to strengthen the recovery of coarse-coal particles.